Childhood cancer incidence and survival in Thailand: A comprehensive population-based registry analysis, 1990–2011 - Serena S. Bidwell (2018)
© 2018 Wiley Periodicals, Inc. Background: Southeast Asia is undergoing a transition from infectious to chronic diseases, including a dramatic increase in adult cancers. Childhood cancer research in Thailand has focused predominantly on leukemias and lymphomas or only examined children for a short period of time. This comprehensive multisite study examined childhood cancer incidence and survival rates in Thailand across all International Classification of Childhood Cancer (ICCC) groups over a 20-year period. Methods: Cancer cases diagnosed in children ages 0-19 years (n = 3574) from 1990 to 2011 were extracted from five provincial population-based Thai registries, covering approximately 10% of the population. Descriptive statistics of the quality of the registries were evaluated. Age-standardized incidence rates (ASRs) were calculated using the Segi world standard population, and relative survival was computed using the Kaplan-Meier method. Changes in incidence and survival were analyzed using Joinpoint Regression and reported as annual percent changes (APC). Results: The ASR of all childhood cancers during the study period was 98.5 per million person-years with 91.0 per million person-years in 1990–2000 and 106.2 per million person-years in 2001–2011. Incidence of all childhood cancers increased significantly (APC = 1.2%, P < 0.01). The top three cancer groups were leukemias, brain tumors, and lymphomas. The 5-year survival for all childhood cancers significantly improved from 39.4% in 1990–2000 to 47.2% in 2001–2011 (P < 0.01). Conclusions: Both childhood cancer incidence and survival rates have increased, suggesting improvement in the health care system as more cases are identified and treated. Analyzing childhood cancer trends in low- and middle-income countries can improve understanding of cancer etiology and pediatric health care disparities.